1993
DOI: 10.1111/j.1651-2227.1993.tb18030.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term growth in children with allergic rhinitis treated with oral antihistamine, depot and intranasal glucocorticosteroids

Abstract: Short-term growth was studied during the grass pollen season with weekly knemometry in 44 schoolchildren with allergic rhinitis. The design was a randomized, parallel group study. After a four-weeks run-in period, the children were allocated to six weeks' treatment with either a single im injection of methylprednisolone acetate 60 mg at the beginning of the period, intranasal budesonide 200 micrograms bid (aerosol spray) or terfenadine tablets 60 mg daily. Treatment with methylprednisolone acetate was open, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(36 citation statements)
references
References 17 publications
(16 reference statements)
2
34
0
Order By: Relevance
“…After 1–2 weeks growth proceeded along pretreatment lines. This is in accordance with our findings in the study of methylprednisolone acetate [7]. …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…After 1–2 weeks growth proceeded along pretreatment lines. This is in accordance with our findings in the study of methylprednisolone acetate [7]. …”
Section: Discussionsupporting
confidence: 83%
“…However, since the marked shortening of lower leg length observed in both cases during the first week after the steroid injection was similar to the shortening found in children treated with an intramuscular injection of methylprednisolone acetate, it must represent a growth-suppressive effect of the steroid injection [7]. This has also been reported in children treated with prednisolone and in children suffering from various forms of catabolic stress, and has been suggested to represent a postural compression of non-growing cartilage and bone [5, 6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are concerns regarding the potential of growth suppression in children by topical corticosteroids, and results vary with the agent. One study of beclomethasone showed growth suppression in children treated for 1 year; another study implicated budesonide; however, no such effects were found with mometasone (Schenkel et al, 2000;Skoner et al, 2000;Wolthers & Pedersen, 1993). As a result, the Food and Drug Administration (FDA) has class-labeled all inhaled and intranasal corticosteroids in pediatric patients, and the Joint Task Force recommends that children receive the lowest effective dose of intranasal corticosteroids and that they be routinely monitored for height (Dykewicz & Fineman, 1998).…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…They published additional studies in order to better define that dosage beyond which inhaled budenoside may be safely used [39, 40], and to investigate the effects of inhaled fluticasone propionate and beclomethasone diproprionate [41]. They investigated short-term growth in children treated with oral antihistamine, and found growth inhibition during treatments with depot and intranasal corticosteroids [98]. Gibson et al [99] published in 1993 that the reduction in leg growth velocity occorred in spite of a significant increase in energy intake and decrease in oxygen requirement.…”
Section: Clinical Implications Of Short-term Growth Measurementsmentioning
confidence: 99%